2014
DOI: 10.1002/brb3.281
|View full text |Cite
|
Sign up to set email alerts
|

Reading acceleration training changes brain circuitry in children with reading difficulties

Abstract: IntroductionDyslexia is characterized by slow, inaccurate reading. Previous studies have shown that the Reading Acceleration Program (RAP) improves reading speed and accuracy in children and adults with dyslexia and in typical readers across different orthographies. However, the effect of the RAP on the neural circuitry of reading has not been established. In the current study, we examined the effect of the RAP training on regions of interest in the neural circuitry for reading using a lexical decision task du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 66 publications
3
56
0
2
Order By: Relevance
“…The RAP training has been found to improve executive functions, such as error monitoring during a lexical decision task [compared to typical readers (TRs) who trained on the RAP)] Horowitz- Kraus and Breznitz, 2013 and working memory and attention abilities (compared to agematched individuals with RD who did not train on the RAP) [50]. A recent Magnetic Resonance Imaging study also found that the RAP training results in increased activation in neural circuits related to executive functions in children with RD during word reading (i.e., in the anterior cingulate cortex) [37]. However, since lexical decision making is a linguistic reading task by nature and the working memory and attention measures in Niedo's study were measured in the linguistic domain, we cannot conclude that the RAP also has a direct effect on executive functions in the nonlinguistic domain, which was the aim of the current study.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The RAP training has been found to improve executive functions, such as error monitoring during a lexical decision task [compared to typical readers (TRs) who trained on the RAP)] Horowitz- Kraus and Breznitz, 2013 and working memory and attention abilities (compared to agematched individuals with RD who did not train on the RAP) [50]. A recent Magnetic Resonance Imaging study also found that the RAP training results in increased activation in neural circuits related to executive functions in children with RD during word reading (i.e., in the anterior cingulate cortex) [37]. However, since lexical decision making is a linguistic reading task by nature and the working memory and attention measures in Niedo's study were measured in the linguistic domain, we cannot conclude that the RAP also has a direct effect on executive functions in the nonlinguistic domain, which was the aim of the current study.…”
Section: Introductionmentioning
confidence: 94%
“…The procedure forces the reader to process words in a fast, holistic manner and 'releases' the bottle-neck in working memory, which enables comprehension. [32] In turn, the readers' ability to read words improves as their mental lexicon becomes more stable and their error monitoring improves [34,32,37]. The RAP training has been found to improve executive functions, such as error monitoring during a lexical decision task [compared to typical readers (TRs) who trained on the RAP)] Horowitz- Kraus and Breznitz, 2013 and working memory and attention abilities (compared to agematched individuals with RD who did not train on the RAP) [50].…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations